POLA HUBUNGAN SOSIAL ANTARA RENTENIR DENGAN NASABAHNYA DI KELURAHAN PALAS KECAMATAN RUMBAI KOTA PEKANBARU - Susilawati, Rossi; Marnelly, T. Romi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The amount of economic demands and necessities of life make people do a variety of ways to fulfill, it is done with the hope to get a better life. There are many ways and effort to the communities to meet their needs, one of them to borrow money. Borrowing money through the creditors more attractive to people, especially in Palas Village Rumbai Subdistrict Pekanbaru City. This study aims to determine how the characteristics of the creditors and the costumers as well as to find out how social relationship formed between the creditors and customers. In this research is descriptive quantitative research, the population in this study were identified community use the service of the creditors in the headman Palas Village Rumbai Subdistrict Pekanbaru City. The study sample as many as 3 creditors and 54 customers ( 50 % ) of the total population using propotional sampling technique is the use of propotional representation. To collect data the researcher used the questionnaire method of observation and documentation as a reference for information in analyzing the data. The result of this research using the quantitative research analysis and described it descriptively. Result of the analysis indicated that the loan sharks attractive by people despite the high interest charged. Generally the creditors are people with relatively high levels of the economy, while customers are the people who rate the economy is relatively low, this requiring a loan to make a living. Through the process of lending and borrowing, there were several social relationship between the creditors and the customers that is trust relationship, communication, exploitation, conflict and interdependence.Key words : the creditor, the customer, social relationship